Polymorphic Relationship of rs7526700, rs2278651, and rs611386 Of SLC30A1 Mothers’ Gene with Mothers’ High Levels of Zinc - Chairunas1, Sjarif Hidajat Effendi2, Harmas Yazid Yusuf3, Eriska Riyanti4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The most common facial malformation in all populations and ethnic groups is Cleft lip and palate (CB/L). Various factors cause nonsyndromic cleft lip and palate abnormalities (CB/L NS) such as interactions between environmental and genetic factors, so that CB/L embryopathy is not clear. Deficiency of Zn with certain severity in pregnant women can be a risk factor for CB/L. The purpose of this study was to analyze the relationship of polymorphism of rs7526700, rs2278651, and rs611386 of the gene SCL30A1 mother with a group of deficiency events of Zinc maternal. The type of this research is an observational study through cross sectional approach with the research subjects are mothers and newborns diagnosed with CB/L NS in the Perinatology Department of Dr. Hasan Sadikin Hospital Bandung and other Network Hospitals. The research was conducted in September 2016 to June 2017 with 34 groups samples. Data were analyzed using fisher’s exact test and correlation test. The results showed that the majority of mothers who became the research respondents aged 25-29 years were 34% and the majority of infants who became the respondents were female as much as 60%, and most types of lip and palate disorders experienced by infants who became the respondents was Unilateral CB/L which is as much as 66%. Furthermore, the results of statistical tests indicated that there was no significant relationship between polymorphism of rs7526700, rs2278651, and rs611386SLC30A1 maternal gene with levels of Zinc maternal